Interleukin-1 and Keratinocyte Growth Factor/Fibroblast Growth Factor-7 Gene Expression in Skin Experimental Irritant Contact Dermatitis Mouse Model Treated with Aqueous Extract of Trachyspermum copticum (L.) Link Seeds - Rasouli, Shima; Karimi, Forouzan; Anissian, Ali; Bandehpour, Mojgan; Kamalinejad, Mohammad (Novelty in Biomedicine, 2018)
Background: In our previous study, the extract of Trachyspermum copticum (L.) Link seeds on gene expression of IFN-γ and TGF-β1 in mouse model with irritant contact dermatitis (ICD), in comparison with cutaneous corticosteroids were evaluated. In that study, in addition to significantly increase of IFN-γ and TGF-β1 genes expression levels in skin samples of "mice with ICD" groups treated with extract in comparison to other groups, histopathologic findings showed substantial improvement of skin color, texture and thickness, and also significant increase in hair follicle number. Therefore, we have decided to study the levels of Interleukin-1 (IL-1) gene expression, which plays a major role in inflammation responses, and Keratinocyte Growth Factor/Fibroblast Growth Factor-7 (KGF/FGF-7), which has growth effect on cells and is an important endogenous mediator of hair follicle growth and development. Materials and Methods: We used autopsy samples of skin lesions obtained from "mice model with irritant contact dermatitis (ICD)" from the previous study. In that study, "mice with ICD" divided in 9 groups and were treated with three concentrations of Trachyspermum Copticum (L.) Link dried seeds, cutaneous hydrocortisone, and fluocinolone acetonide. Then from the first day until the 10th day of treatment, clinical signs and histopathologic investigations were investigated. In the present study, using Real-Time PCR, the levels of IL-1 and KGF/FGF-7 genes expression in skin samples of inflammation site in above mice groups were studied. Statistical analysis, using one -way ANOVA, were performed. Level of significance was set at 0.05. Results: The IL-1 gene expression showed a significant difference between groups: IL-1 gene expression levels in mice with ICD treated with extract and corticosteroids were higher than the other groups (p=0.0001). While in untreated "mice with ICD", no significant differences were observed. Also, during the treatment, there was a considerable increase in levels of IL-1 gene expression in groups treated with the extract at a rate of at least 2 to 3-fold in comparison with the "healthy untreated mice" group. The levels of KGF/FGF-7 gene expression in "mice with ICD" groups treated with the extract showed significance difference (p=0.014); also there was a meaningful difference in "mice with ICD" groups treated with cutaneous corticosteroids (p=0.004). While, in "untreated mice with ICD" group there were a significant decrease in the levels of KGF/FGF-7 gene expression in comparison with "healthy untreated mice" group (p=0.0001). Also, changes in the levels IL-1 and KGF/FGF-7 gene expressions in each group in different days were seen. Conclusion: In this study, significant changes in the IL-1 and KGF/FGF-7 genes expression levels in the skin samples with inflammation, were associated with an increase in the rate and speed of improvement of contact dermatitis, more favorable conditions of the healed skin (in terms of color, consistency, and thickness), and a remarkable increase in the number of hair grown on the site of dermatitis (compared with control groups, and even groups with corticosteroid therapy).